1989
DOI: 10.1007/bf00314410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cannabinoids on spasticity and ataxia in multiple sclerosis

Abstract: The chronic motor handicaps of a 30-year-old multiple sclerosis patient acutely improved while he smoked a marihuana cigarette. This effect was quantitatively assessed by means of clinical rating, electromyographic investigation of the leg flexor reflexes and electromagnetic recording of the hand action tremor. It is concluded that cannabinoids may have powerful beneficial effects on both spasticity and ataxia that warrant further evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(52 citation statements)
references
References 14 publications
0
48
0
4
Order By: Relevance
“…These include the well known psychotropic effects, some adverse effects (e.g., memory loss, sedation, and motor impairment), and several beneficial effects (e.g., relief of muscle spasticity, analgesia, and reduction of inflammation) (Consroe et al, 1997;Hall and Solowij, 1998;Hampson and Deadwyler, 2000;Watson et al, 2000;Solowij et al, 2002). Because marijuana produces remarkable beneficial effects, patients with multiple sclerosis, for example, commonly use this plant as a therapeutic agent; however, we still lack essential information on the mechanistic basis of these beneficial effects (Lyman et al, 1989;Meinck et al, 1989;Wirguin et al, 1994;Martyn et al, 1995;Baker et al, 2000Baker et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…These include the well known psychotropic effects, some adverse effects (e.g., memory loss, sedation, and motor impairment), and several beneficial effects (e.g., relief of muscle spasticity, analgesia, and reduction of inflammation) (Consroe et al, 1997;Hall and Solowij, 1998;Hampson and Deadwyler, 2000;Watson et al, 2000;Solowij et al, 2002). Because marijuana produces remarkable beneficial effects, patients with multiple sclerosis, for example, commonly use this plant as a therapeutic agent; however, we still lack essential information on the mechanistic basis of these beneficial effects (Lyman et al, 1989;Meinck et al, 1989;Wirguin et al, 1994;Martyn et al, 1995;Baker et al, 2000Baker et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…2 It was not before the 1960s that the chemical structure of the main active compound of cannabis, (À)-trans-D 9 tetrahydrocannabinol (THC, dronabinol) was characterized, allowing first clinical studies with exact doses. Surveys among patients with multiple sclerosis and spinal cord injury (SCI), who used cannabis to treat their symptoms, [3][4][5][6] case reports 7,8 and small clinical studies with dronabinol and other synthetic cannabinoids [9][10][11][12][13] suggest that cannabis and single cannabinoids may be useful medicines in spasticity and spasms.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been no published clinical trials on effects of cannabinoids in ataxia and potential effects on ataxia are confined to case report data in patients with MS with associated ataxia. Here, oral Δ 9 -THC or marijuana have been reported to improve motor coordination in some patients with MS [89,92]. These reports contrast with the clear exacerbating effects of CB 1 R agonists in animals and suggest that investigations with different cannabinoids in patient populations with specific ataxias are needed.…”
Section: Ataxiamentioning
confidence: 83%
“…Involvement of the endocannabinoid system acting at CB 1 R in the pathogenesis of MS have been supported by several studies [87][88][89][90]. There are now several lines of evidence indicative of therapeutic potentials of cannabinoids in the control of MSrelated symptoms, including tremor, which remains difficult to manage with current medications (e.g., carbamazepine, propranolol, primidone, and gluthetimide) [12,89,91,92]. Following this premise, De Lago et al [93] have shown that the nonselective cannabinoid agonist WIN 55,212-2 ameliorated neurological disability, tremor, and spasticity in the chronic relapsing experimental autoimmune encephalomyelitis murine model of MS [92].…”
Section: Cannabinoids and Ms-related Tremormentioning
confidence: 93%
See 1 more Smart Citation